2014
DOI: 10.1080/14616688.2014.959991
|View full text |Cite
|
Sign up to set email alerts
|

Impact of culture on perceptions of landscape names

Abstract: This study examines the impact of culture on landscape-name perceptions of tourists from China, United States, and Europe utilizing both Hofstede's and Hall's cultural typologies. Data for this study were collected from visitors to two national parks in China. Culture is found to have a significant impact on both sub-dimensions of understanding (legibility and coherence) and involvement (mystery and diversity). Findings suggest that tourists from different cultures are likely to interpret landscape names diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
(55 reference statements)
2
2
0
1
Order By: Relevance
“…Consistent with these previous findings, Zhang et al (2015) confirmed that tourists' cultural backgrounds lead to diverse interpretations of landscape names and influenced their preferences. Specifically, tourists from cultures with high levels of power distance and low levels of individualism prefer landscape names that are mystic, dreamy, fictive, ingenious, original, and poetic, whereas their counterparts (i.e., tourists from cultures with low levels of power distance and high levels of individualism) prefer names that simply describe the landscape.…”
Section: Cultural Differences In Tourist Experiencessupporting
confidence: 87%
“…Consistent with these previous findings, Zhang et al (2015) confirmed that tourists' cultural backgrounds lead to diverse interpretations of landscape names and influenced their preferences. Specifically, tourists from cultures with high levels of power distance and low levels of individualism prefer landscape names that are mystic, dreamy, fictive, ingenious, original, and poetic, whereas their counterparts (i.e., tourists from cultures with low levels of power distance and high levels of individualism) prefer names that simply describe the landscape.…”
Section: Cultural Differences In Tourist Experiencessupporting
confidence: 87%
“…Furthermore, location also plays an important role in landscape perception. This research shows that people from different countries may hold various opinions about a landscape, consistent with previous studies [68,98,117]. In the study presented by [68], Australian participants fixated more frequently and for longer durations on tourism images than Chinese participants.…”
Section: Demographic Differences In Mountain Landscape Perceptionsupporting
confidence: 90%
“…The literature review by Pike (2002), of destination image articles, reveals that 6 of the 142 published destination image papers showed an explicit interest in affective images, whereas cognitive image is a widely accepted, solid destination measurement base. The majority of destination image studies have analyzed cognitive perceptions by focusing on tangible attributes of destinations (Pearce, 1977(Pearce, , 1982Gartner, 1989;Pike, 2002;Beerli and Mart ın, 2004a;Lee and Lee, 2009;Agapito et al, 2013;Zhang et al, 2014;Stylos et al, 2016Stylos et al, , 2017Stylidis et al, 2017;Lin et al, 2018).…”
Section: Cognitive Factors Affecting Destination Image Perceptionmentioning
confidence: 99%